(untitled) (Revista Linhas, 2007)
O processo de implementação do Sistema Único de Saúde –SUS e a prática conselhista na área da saúde estão sofrendo com os limites do Movimento de Reforma Sanitária. As análises desses limites, acontecem a partir da fala de conselheiros municipais de saúde, que estão vivendo a responsabilidade de juntamente com o poder público implementar o SUS. Mas como não participaram de todo este movimento de reivindicação e reconhecimento dos direitos, agora tendo a responsabilidade de implementá-los sentem a falta destas referências e acabam por reproduzir práticas tradicionais de nossa cultura política. Uma proposição de pedagogia política que possa ser construída no espaço dos Conselhos, pode ser uma forma de preparar os diferentes segmentos sociais para participarem efetivamente destes espaços, socializarem tal proposta política e serem sustentação orgânica de tais princípios junto a sociedade. Abstract:The construction of today’s health policies : recognizing its limits in the counselors’ speeches . The process of implantation of the T-lealth United System (SUS) and the counselors’ practice in the health area have been suffering with the lirnits established by the Sanitary Reform Movement. The analysis of these limits is based on the speeches of municipal health counselors, who have the responsability of along, with the public power, implant the SUS. However, as they didn’tjoin this rnovement ofreivindication and recognition ofrights since its beginning, and now have the responsability of irnplariting them, they rniss these references and end up reproducing traditional practices in our political habits. The proposition of politicalpedagogy, to be built in the Councils’ space, could be a way to prepare the different social groups to participate actively in these spaces, to socialize such political proposal and to be the organic support of such principies along the society